Baicalin Depresses the Sympathoexcitatory Reflex Induced by Myocardial Ischemia via the Dorsal Root Ganglia - Zou, Lifang; Han, Xinyao; Liu, Shuangmei; Gong, Yingxin; Wu, Bing; Yi, Zhihua; Liu, Hui; Zhao, Shanhong; Jia, Tianyu; Li, Lin; Yuan, Huilong; Shi, Liran; et al. (Frontiers in Physiology, 2018)
Myocardial ischemia is one of the major causes of death in cardiac diseases. Purinergic signaling is involved in bidirectional neuronal-glial communication in the primary sensory ganglia. The sensory neuritis of cardiac afferent neurons in cervical dorsal root ganglion (cDRG) interacts with cardiac sympathetic efferent postganglionic neurons, forming feedback loops. The P2Y12 receptor is expressed in satellite glial cells (SGCs) of DRG. Baicalin is a major active ingredient extracted from natural herbal medicines, which has anti-inflammatory and strong anti-oxidation properties. In this study we investigated the effect of baicalin on P2Y12 receptor in the cervical DRG SGC-mediated sympathoexcitatory reflex, which is increased during myocardial ischemia (MI). The results showed that the expression of P2Y12 receptor mRNA and protein in DRG, and the co-localization values of P2Y12 receptor and glial fibrillary acidic protein (GFAP) in cDRG SGCs were increased after MI. The activated SGCs increased IL-1β protein expression and elevated Akt phosphorylation in cDRG. Baicalin treatment inhibited the upregulation of the P2Y12 receptor, GFAP protein and Akt phosphorylation in cDRG neurons/ SGCs. The stellate ganglia (SG) affect cardiac sympathetic activity. Baicalin treatment also decreased the upregulation of the P2Y12 receptor, GFAP protein in the SG. The P2Y12 agonist, 2Me-SADP, increased [Ca2+]i in HEK293 cells transfected with the P2Y12 receptor plasmid and SGCs in cDRG. These results indicate that application of baicalin alleviates pathologic sympathetic activity induced by MI via inhibition of afferents in the cDRG.